Shadows of Uncertainty: When Pneumonia Isn’t Pneumonia - Likith Ashok Gandhi; Pruthu Dhekane; Bharat Purandare; Prayag Parkishit; Rasika Joshi; Riddima Shah; Sarvesh Bhimavat (International Journal of Pathogens, 2026)
Pneumonia is a common medical condition encountered in hospitalized patients and remains a cause of morbidity worldwide. Identifying and initiating appropriate treatment in febrile patients who present with respiratory symptoms and radiographic infiltrates, reduce hospital stay, minimize complications, and lower healthcare costs. However, the assumption that every pulmonary infiltrate or opacity seen on a radiological imaging represents an infectious process such as pneumonia can lead to misdiagnosis, unnecessary investigations, prolonged hospital admissions, and inappropriate use of antibiotics. A wide range of noninfectious pulmonary conditions can produce radiologic findings that closely resemble pneumonia, making accurate diagnosis challenging. This report presents the case of a 52-year-old man who arrived with complaints of progressive exertional dyspnea and a persistent nonproductive cough. Based on his clinical presentation and initial imaging findings, he was diagnosed with community-acquired pneumonia and started on broad-spectrum antibiotic therapy. Despite adequate treatment, his symptoms failed to improve, and repeat evaluations showed no significant clinical or radiological resolution. Chest radiography revealed dense, coalescent opacities involving nearly the entire right lung, raising concern for an alternative underlying pathology. To further investigate the cause of his non-resolving condition, flexible bronchoscopy with transbronchial lung biopsy was performed. Histopathological examination ultimately confirmed the diagnosis of cryptogenic organizing pneumonia, a rare inflammatory lung disorder that can closely mimic infectious pneumonia in both symptoms and imaging appearance. Following initiation of appropriate corticosteroid therapy, the patient demonstrated marked clinical and radiological improvement. This case emphasizes the importance of reconsidering the diagnosis in patients who do not respond to standard antimicrobial therapy. It highlights that cryptogenic organizing pneumonia and other noninfectious pulmonary diseases should be included in the differential diagnosis of presumed pneumonia, particularly when the clinical course is atypical or unresponsive to treatment. Early recognition and appropriate diagnostic evaluation are essential to ensure timely and effective management.
Keywords: Bronchiolitis obliterans organizing pneumonia; case report; cryptogenic organizing pneumonia; diagnostic work-up; treatment